2022
DOI: 10.3390/healthcare10091800
|View full text |Cite
|
Sign up to set email alerts
|

Sulphurous Crenotherapy Is Effective at Reducing Pain and Disability in Overweight/Obese Patients Affected by Chronic Low Back Pain from Spine Osteoarthritis

Abstract: Crenotherapy is recognized as being effective in patients with osteoarthritis of the spine, but to date there is no indication if it is effective for patients who are overweight or obese. The aim of this study is to evaluate the efficacy of sulphurous crenotherapy on pain and disability in overweight/obese subjects affected by chronic low back pain from spine osteoarthritis. Forty-three patients (63 ± 8.8 years) affected by chronic low back pain from lumbar spine osteoarthritis were enrolled in this study. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Crenotherapy or spa salus per aquam has therapeutic effects on various disorders, especially in those triggered by oxidative stress, and in some cases, they represent an alternative approach to standard pharmacological treatments [14][15][16][17][18][19][20][21][22]. Based on their ionic compositions, mineral waters can be classified as sulfureous, sulfate, bicarbonate, sodium chloride, ferrous arsenic waters, and others [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Crenotherapy or spa salus per aquam has therapeutic effects on various disorders, especially in those triggered by oxidative stress, and in some cases, they represent an alternative approach to standard pharmacological treatments [14][15][16][17][18][19][20][21][22]. Based on their ionic compositions, mineral waters can be classified as sulfureous, sulfate, bicarbonate, sodium chloride, ferrous arsenic waters, and others [23].…”
Section: Discussionmentioning
confidence: 99%
“…Crenotherapy with sulfureous mineral water exerts beneficial effects in several diseases and also improves cellular redox state in both animal models and humans [2,[14][15][16][17][18][19][20]. Moreover, the sulfureous hydropinotherapy cycle significantly reduces circulating levels of reactive oxygen metabolites (ROMs) in patients with gastrointestinal disorders, likely protecting them from oxidative stress [21]. Hydropinotherapy relies on drinking mineral water in the morning by sipping during the fasting state to overcome possible interferences with digestive processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-clinical studies and clinical trials have shown that spa interventions can be beneficial in subjects with rheumatic diseases [ 13 , 14 , 15 , 16 ]. The effects of immersion and exercise in thermal mineral-rich water on symptoms and inflammation appear to be superior and longer-lasting than the effects of hydrotherapy [ 14 , 17 , 18 , 19 , 20 ]. Furthermore, preliminary studies are evaluating the effects of thermal mineral-rich water on the skin’s microbiome, since bathing in thermal water could act on certain bacteria of the skin [ 21 ].…”
Section: Introductionmentioning
confidence: 99%